Airway Management of Patient with Smith-Lemli-Opitz Syndrome - Ahmet Küçük; Harun Aydoğan; Mahmut Alp Karahan; Hasan Hüsnü Yüce; Nuray Altay; İsmail İynen (İstanbul Medical Journal, 2015)

(untitled)
Smith–Lemli–Opitz syndrome (SLOS) is a rare autosomal recessive syndrome presenting with multiple congenital anomalies and mental retardation associated with low plasma cholesterol levels. Two forms have been recognized based on clinical course and severity: the classical SLOS (type I) and the lethal acrodysgenital syndrome (type II). SLOS type I clinical symptoms are less severe, and life expectancy is longer. SLOS type II is also accompanied by multiple congenital anomalies, and the prognosis is poor, which is lost within weeks. Micrognathia, cleft palate, including large and abnormal stiff tongue, and typical dysmorphic facial features are some of the major causes for the difficult airway in this syndrome. In this case report, we discussed the airway management of a child with SLOS type I who underwent bilateral ear tube insertion.